How Far Has The Talent Management Helped? a Central Java Government Experience - Arisandi, Sindi; Saadah, Maratun (Universitas Muhammadiyah Mataram, 2023)
This study provides a deep analysis of the contextual variables that affect the Central Java Provincial Government's best utilization of talent pools are looked at. Talent pools are collections of high-performing workers who have been selected for taking on more responsibility and occupying key roles within the company. Since public sector organizations are constantly expected to provide effective and efficient public services while operating in a financially constrained environment and facing a persistent talent shortage as well as rising competition for talent, effective talent pool utilization is especially important in an emerging economy. The study investigates the contextual elements within a local government that could potentially limit the best implementation of a talent management strategy. It does this by drawing on talent management theory and basing its findings on a case study with interviews conducted with thirteen key individuals within the Central Java Provincial Government. The results of this study show that the Central Java Provincial Government's use of talent pools in the public sector is not optimal due to a number of factors, such as the creation of talent pools that do not meet needs, the absence of participant roles, and the absence of an understanding of the appraisal process. The absence of explanation for maintaining abilities is a further element identified. These results are known to be impacted by a lack of resources, a lack of opportunities for talent development, a lack of support from and engagement from leaders, and an incomplete deployment of talent management systems.